PENDIDIKAN GURU AGAMA ISLAM DI PERGURUAN TINGGI UMUM NEGERI (Studi Komparatif antara Universitas Negeri Jakarta (UNJ) dengan Universitas Pendidikan Indonesia (UPI) Bandung) - Muhammad Munadi (Cendekia: Kependidikan dan Kemasyarakatan, 2017)
This study examines in depth the design and preparation process of PAI (Education of Islamic Religious) teacher candidates from the curriculum composition. This research uses research method of curriculum text study that exist in two institutions preparing PAI teacher that is Universitas Negeri Jakarta (UNJ) and Universitas Pendidikan Indonesia (UPI) Bandung. The text under study is the curriculum that is on the web of each college. Data analysis using qualitative descriptive technique. The results of research include the following: First, the preparation of Islamic religious education teachers both in UPI Bandung and UNJ focus on strengthening the mastery of Islamic content than the provision of learning methodology materials. But the different depths, UPI more in-depth study of Islam because it is a study program while the UNJ is concentrated. Second, the concept of pedagogical content knowledge as an alternative bid that must be developed by LPTK in graduated professional teachers who have a balance in mastery of material and pedagogic abilityتدرس هذه الدراسة بعمق عملية تصميم وإعداد المرشحين لمعلمي الدين الإسلامي من منظور تكوين المناهج الدراسية.  يستخدم هذا البحث منهج دراسة نص المناهج الدراسية التي توجد في الجامعتين اللتان تقومان بإعداد معلمي الدين الإسلامي فهما جامعة بندونج الحكومية للتربية وجامعة جاكرتا الحكومية.  النص قيد الدراسة هو المناهج التي هي على شبكة الإنترنت من كلتا الجامعتين. وتحليل البيانات باستخدام تقنية وصفية النوعية. وتشمل نتائج البحث ما يلي: أولا، إن إعداد معلمي التربية الدينية الإسلامية في كل من جامعة بندونج الحكومية للتربية وجامعة جاكرتا الحكومية تركزان على تعزيز إتقان المحتوى الإسلامي بالنسبة إلى توفير مواد منهجية التدريس. ولكن الأعماق المختلفة، كانت جامعة بندونج أكثراهتماما بدراسة متعمقة للإسلام لأنه هو قسم الدراسة في حين جامعة جاكرتا مجرد شعبة من القسم. ثانيا، مفهوم معرفة المحتوى التربوي كمحاولة بديلة التي يجب تطويرها من قبل لبتك (LPTK) في تخريج المعلمين المهنيين الذين لديهم كفاءة  في إتقان المواد والمناهج التربوية.